PENGARUH PEMBERIAN SUSU KEDELAI (GLYCINE MAX L. MERR) TERHADAP KADAR KOLESTEROL TOTAL PADA WANITA MENOPAUSE (STUDI PADA IBU-IBU PENGAJIAN AISYIYAH RANTING MELATI MEDAN) - ABD WAHAB DALIMUNTHE; AMELIA EKA DAMAYANTY (JURNAL ILMIAH KOHESI, 2020)
In postmenopausal women, estrogen secretion decreased due to ovarian atrophy. Increased levels of total cholesterol occurafter menopause or after ovarectomy. The use of soybean phytoestrogens shows the effect of reducing lipid levels inmenopausal women. This study aimed to see the effect of giving soy milk to total cholesterol levels in postmenopausalwomen in mothers of Aisyiyah group. This experimental study used the design of one group pretest and posttest. Subjectswere 30 menopausal women aged 43-76 years who were given 250 mL soy milk. And data was processed using Wilcoxontest. The mean total cholesterol level before treatment was 241,03 mg/dL and after treatment 224.70 mg/dL, with adifference in the average reduction in total cholesterol levels of 16,33 mg/dL with p 0,002 (p<0,005). There is an effect ofgiving soy milk to total cholesterol levels in menopausal women.